Exploring implications of Covid-19 on children and caregivers in informal kinship care in Shibuyunji Zambia - Banda, Beatrice (2021)
This study aimed to explore the impacts of COVID-19 among children and caregivers in informal kinship care households. The study sought to establish the experiences of children and their caregivers before and during the pandemic. A qualitative exploratory research design was employed. 10 key informants (5 children and 5 caregivers) who had lived in kinship care before and during the pandemic were selected using purposive sampling with the help of a research assistant. Data were collected through in-depth interviews conducted online via Zoom, and data was analyzed using thematic analysis. According to the study findings, children and caregivers were already vulnerable before the pandemic began as they could not meet their basic needs. The COVID-19 exacerbated their situation because they could not generate an income due to the restrictions imposed to combat the pandemic. For example, those who ran small-scale businesses could no longer continue as before. The main challenges that children and caregivers faced were lack of enough food to eat and money to pay children’s school fees. To cope with the pandemic effects, some children took on informal jobs within their village to help provide for their kinship care families. The study found that Zambia's COVID-19 Emergency Cash Transfer (ECT) program needed to be expanded to benefit more vulnerable families. Furthermore, kinship care is the most common and widely practiced type of alternative care in Zambia, but there are not enough programs to assist vulnerable kinship care families.